Civil liability for carriers of Coronavirus infection - Lecture Dr. Arshed Taha Hattab, Lecture Dr. Faisal mohammed abed, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
The study is based on research into the civil liability for the transmission of covid-19 in Iraqi law, by identifying the definition of infection and the definition of the disease, what is covid-19, what methods of propagation and transmission, and what symptoms cause the patient, all we addressed in the first research. The second research is devoted to the provisions of civil responsibility for the CORONA virus, and the search for its pillars, namely error and damage, and this causal relationship and what is wrong, what damage is done to the victim of mers-co777 transmission, what is the damage caused, the causal relationship between the offender's fault and the damage, and whether the transmission is intentional or unintentional. The study concluded with the legal implications of that liability, which was limited to in-kind implementation and compensation. Finally, we concluded the research with a number of findings and recommendations, which may be a basis for the legislator to address this modern problem.